A Case Study of Cryptosporidium–like Disease in American Cliff Swallows (Petrochelidon pyrrhonota) - Jackman, Trish; Meier, Jane (Wildlife Rehabilitation Bulletin, 2013)
Twenty–six American cliff swallows became ill with respiratory signs that included eyelid edema and erythema, ocular and nasal discharge, dyspnea, and visual impairment. The birds displayed a depressed fluffed appearance, dehydration, and anorexia. Over a three–month period, 21 of the 26 birds died. The disease mimicked a Mycoplasma spp. infection. Treatment with topical ophthalmic antibiotic and tylosin tartrate produced a temporary improvement of clinical signs, but did not have a lasting effect. Necropsy findings indicated a Cryptosporidium–like disease. This protozoa is pathogenic in both mammals and birds, but is more commonly found in mammals, where it targets the gastrointestinal system. In birds however, it appears to cause respiratory involvement almost exclusively. The remaining five birds were quarantined and treated with paromomycin sulfate, but treatment proved unsuccessful and these birds also died. Mortality was 100 percent in this outbreak.